Модифицированный метод наименьших квадратов в обобщенно-инвариантной постановке - Булычев, Ю.Г.; Елисеев, А.В. (Проблемы управления и информатики, 2006)
Розв’язано задачу обробки вимірів з динамічними перешкодами спостереження. Отриманий метод інваріантний до кусочнонеперервних перешкод детермінованої структури з невідомими параметрами. Метод не вимагає розширення простору стану і забезпечує підвищення оперативності розв’язку задачі оцінювання. Наведено ілюстративний приклад, що підтверджує ефективність методу. A problem of processing measurement containing dynamic observation interferences is solved. The method obtained has the property of invariance to the piecewise-continuous interferences of the deterministic structure with unknown parameters. This method does not require the broadening of the state space and provides the increase of the operative speed in solving the estimation problem. An illustrative example is given to verify the efficiency of the method.